BUDAYA HIDUP BERSIH MELALUI âMASâ (MANAJEMEN AIR DAN SAMPAH DI DESA CANGKRING - Jamaludin, Ahmad; R, Royani; Maulana, Taufiq; E., Eviyanti; Salamah, MarÃ¢Â€Â™atus (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Trash and water until now has always been a problem, trash seen as something dirty and should be discarded. When carelessly discarded will be a source of environmental contamination and human resources for the disease, even when disposed in place does not mean the problem was solved, a new problem arises because landfills. Therefore, to change the perception of waste, which must be disposed of into something that can be exploited. This condition occurs in Cangkring Village district. Cantigi Kab. Indramayu, some people have a bad habit cangkring village is throwing garbage on the banks of rivers, and the surrounding environment, lack of information and lack of facilities resulted in low awareness of the hedge on the health problems they are experiencing a skin disease that is 3.23%, 1.35% deworming, 1.25 cholera, dengue fever 0.4%, 13.3% diarrhea, hepatitis 0.3%, and 0.07% of malaria. (Health Research Indramayu: 2007). The method is performed in the execution of the program begins with early socialization, training cadre includes technical debriefing program, composting training, training and training craft manufacture water treatment. Once equipped with the next activity is the dissemination and implementation of public hygiene MAS program which was facilitated by a team from making garbage sorting, water and waste management and marketing. All stages aims to encourage people to improve clean lifestyle with community development activities through the management and utilization of waste and clean water. Results that have been achieved from this activity is the production of handicraft products from packaging waste and water and can be sold for cash as well as increasing awareness of the organization and the quality of public health.